Synthesis of the Biofuel Additive 1,1-Diethoxybutane in a Fixed-Bed Column with Amberlyst-15 Wet - Maria João Regufe (2016)
The synthesis of 1,1-diethoxybutane (DEB) through the acetalization reaction between ethanol and butyraldehyde was studied in a fixed-bed adsorptive reactor packed with Amberlyst-15 wet. The miscibilities of reactants and water were evaluated and breakthrough experiments with nonreactive pairs of ethanol-water and ethanol-DEB were performed. The parameters of the isotherms were fitted by a Langmuir competitive model. Synthesis of the acetal was carried out with mixtures of ethanol and butyraldehyde at different molar ratios. The dynamic behavior of the fixed-bed adsorptive reactor was described by a mathematical model developed taking into account the reaction kinetics, adsorption mechanisms, mass transfer resistances, and velocity variations.